EXTERNAL FINANCIAL FLOWS, FISCAL POLICY AND ECONOMIC SUSTAINABILITY IN NIGERIA: INSIGHTS FROM SOLOW GROWTH HYPOTHESIS (Malaysian Management Journal, 2025)
The attainment of the Sustainable Development Goals (SDGs), introduced by the United Nations leaders in 2015, is anchored on three pillars: economic, social, and environmental sustainability. Economic sustainability refers to the capacity to enhance the overall income and output of all economic agents within the circular flow—both in the present and into the future. This study examines the effect of external financial flows and fiscal policy (internal flows) on economic sustainability in Nigeria, within the framework of the Solow Growth Hypothesis. The study utilises secondary data sourced from the World Development Indicators and the Central Bank of Nigeria's Statistical Bulletin, spanning the period from 1991 to 2022. External financial flows are represented by foreign direct investment, foreign aid, remittances, net exports, and external debt, while fiscal policy is captured through government expenditure on education, government expenditure on health and tax revenue. Economic sustainability is proxied by GDP per capita income. The findings reveal that foreign direct investment and remittances have a positive and significant effect on GDP per capita income, whereas net exports exhibit a negative and significant effect. With respect to fiscal policy, government expenditure on health and tax revenue are found to have a positive and significant impact on GDP per capita income. The study concludes that foreign direct investment, net export and remittances when effectively managed and strategically channeled, have the potential to enhance Nigeria’s economic sustainability. Furthermore, fiscal policy measures particularly capital expenditure in health and improved tax revenue generation can play a crucial role in sustaining long-term economic growth. It is therefore recommended that the government create a viable market and a conducive business environment to attract foreign direct investment and strengthen fiscal management frameworks.